Oaths in The Short Chapters of Al-Mufaṣṣal from the Qur'an (Analytical Study based on the Tafsir Mafatih Al-Ghaib): القسم في قصار المفصل من القرآن (دراسة تحليلية من تفسير مفاتيح الغيب) - Dafina Salsabila; Akhmad Sulthoni; Akhmadiyah Saputra; Madiha Syarifah Balqis (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD, 2025)
This study aims to explore the meanings contained in the oath verses within those found in the surahs from Adh-Dhuha to An-Nas (qiṣar al-mufaṣṣal). The research adopts a qualitative approach using the method of library research. The analytical method employed in this study is the thematic method focusing on a particular scholar. Based on the discussion, it is evident that al-Rāzī possesses a distinctive methodology in interpreting verses, including the oath verses. His methodology is characterized by a systematic approach in initiating interpretation, explaining the differences in Qirā'at (variant readings of the Qur'an), citing interpretations from various classical scholars, and utilizing imaginary dialogue. This finding highlights al-Rāzī's distinctive approach in elucidating moral values embedded within religious teachings through the interpretive analysis of oath-related verses. The oath verse in Surah Adh-Dhuha teaches that worldly life is never free from changes and trials. In Surah At-Tin, it emphasizes the sanctity of sacred places and the honor of the prophets associated with the oath. The oath verse in Surah Al-‘Adiyat highlights that Allah swears by the horses of the warriors due to their significant benefits in both worldly and religious affairs. This also serves as an indication that horses should be used not for pride and luxury but for the purpose of jihad.